Contemporary Perspective on Child Psychology and Education - Çetinkaya, Şenay (IntechOpen, 2018)
In contemporary understanding, the working areas of children's psychology are expanding considerably. The mental health of the children ensures that they are able to use their developmental abilities, cope with difficulties in life, be productive and be creative, and demonstrate cognitive, emotional, and behavioral characteristics appropriate to their developmental turn. This research was conducted to be able to identify behavioral disorders that may be a sign of children's mental problems and to shed light on the resolution of possible problems by facilitating the follow-up of psychosocial developments during the period of growth. This book presents an overview of the contemporary approaches in the departments of child education and psychology, with the hope of them growing up as happy, peaceful, balanced, thoughtful confident and successful individuals.